Tectono-stratigraphic evolution of the northeastern sector of the Ñirihuau Basin, North Patagonian Andes, Argentina: Insights from sedimentology and geochronology data of the Ñirihuau Formation - Santonja, Camila (2021)
Fil: Santonja, Camila. Universidad de Buenos Aires, Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET), Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires (IGEBA), Ciudad Universitaria, Pabellón II, Intendente Güiraldes 2160 (C1428EHA), Buenos Aires, Argentina.